(untitled) (Ornitología Colombiana, 2021)
We present the first nest description for the Gold-ringed Tanager (Bangsia aureocincta) and include notes on parental care. The nest is a large domed ball constructed of moss, whereas the nest lining is constructed of rootlets. We observed three adults attending the nest, the first evidence of cooperative breeding in a mountain tanager. Nest architecture is variable within Bangsia and mountain tanagers but may still be phylogenetically informative within tanagers and allies. The main breeding season of the Gold-ringed Tanager in western Colombia is February-July.